A qualitative study on the perception of undergraduate nursing students on online learning during the Covid-19 pandemic at a public university in Malaysia / Muhammad Hibatullah Romli - Muhammad Hibatullah, Romli (2021)
The COVID-19 pandemic and Movement Control Order have restricted learning activities in traditional face-to-face classrooms. Subsequently, these learning activities have shifted to full online learning, and these activities are conducted in the student’s own environment namely dorm room and home. The present researcher conducted a meta-synthesis, and the result shows that full online learning is receiving resistance, however, it begin to gain better reception. Past studies show that online learning is a potential approach in allowing active and dynamic learning experience especially on the acquisition of theoretical knowledge, despite having limitations to developing technical skills. Therefore, the present study aimed to investigate the perception of undergraduate nursing students on online learning during the COVID-19 pandemic. A qualitative study involving focus group discussions and in-depth interviews was conducted. Nursing students from one Malaysian public institution were recruited. Ethical approval was obtained, and the participants were recruited via social media platform (i.e., WhatsApp, email). A total of twenty-one participated in four group and three individual interviews. The sessions were conducted online via Zoom or Google Meet applications, and these were recorded. The data were analyzed using thematic analysis with assistance of QDA Miner Lite software. Trustworthiness on the findings were done via credibility (giving the findings summary to the participants for feedback a.k.a. member-checking), confirmability (discussion with researchers and note-takers) and transferability (comprehensive representation to the targeted population). Three themes with a total of ten sub-themes were generated: (i) Full online learning has ramification on life (it’s about life; blurred division on education life and personal life; non-conducive environment for learning; health and well-being; human is an adaptable being while transition takes time), (ii) full online learning is a medium of iv teaching and learning delivery but with several concerns (the silver living of full online learning; challenges associated with full online learning; coping strategy in handling full online learning), and (iii) Foundation in teaching and learning is the key (role of the educator; teaching and learning approaches; motivation and regulation). Full online learning during this pandemic is a life event and a transition process from conventional to digital learning. However, the importance of teaching concepts such as educators’ quality, teaching and learning approaches, and supportive learning environment remains intact and relevant; hence modification required to suits with online learning needs. Based on the lessons learnt in dealing with full online learning during the COVID-19 pandemic, these lessons learnt may also essential for both learners and educators to be equipped with technology skills in embracing the national aspiration for Industrial Revolution 4.0 and National Education Policy. A practice framework is successfully developed from the present study. Further investigation such as replication of the study to other populations may enhance the generalizability of the findings, while experimental research of single-subject research design is suggested to assess the efficacy of the practice framework.